Effects of Carbohydrate and Dietary Fiber Intake, Glycemic Index and Glycemic Load on HDL Metabolism in Asian Populations - Yanai, Hidekatsu (Elmer Press, 2014)
High-density lipoprotein (HDL) is a lipoprotein which has anti-atherogenic property by reverse cholesterol transport from the peripheral tissues to liver. Low HDL-cholesterol (HDL-C) levels are associated with the development of coronary artery diseases (CADs). Various epidemiological studies have suggested that the development of CAD increase in individuals with less than 40 mg/dL of HDL-C. In spite of accumulation of evidences which suggest a significant association between low HDL-C and cardiovascular diseases, effects of dietary factors on HDL metabolism remained largely unknown. There may be interracial differences in effects of dietary factors on HDL metabolism. Here we reviewed published articles about effects of carbohydrate and dietary fiber intake, glycemic index (GI) and glycemic load (GL), on HDL-C metabolism, regarding meta-analyses and clinical studies performed in Asian population as important articles. Low carbohydrate intake, GI and GL may be beneficially associated with HDL metabolism. Dietary fiber intake may be favorably associated with HDL metabolism in Asian populations.